Evaluasi Proses Optimasi Sumber Daya, Pengelolaan Sumber Daya Manusia, dan Pengelolaan Operasional pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu DKI Jakarta Menggunakan Kerangka Kerja COBIT 5 - Intan Camila; Admaja Dwi Herlambang; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (PTSP) DKI Jakarta had a vision to be a Jakarta citizens licensing solutions with the several missions that indicated that DPM PTSP provided a quick response services. It indicated that DPM PTSP must had sufficient and capable human resources, the application of optimal information technology and operational activities that run smoothly. In order to measure the optimal value of information technology resources, human resources and operational activities, a capability level assessment carried out in EDM04 (Ensure Resource Optimization) process, APO07 (Manage Human Resource) process and DSS01 (Manage Operations) process using the COBIT 5 framework. The capability level assessment carried out sequentially from level 0 Incomplete Process to level 5 Optimizing Process, analyzed the gap between capability level and targeted level, and provided the recommendations as an improvement of organizational's quality. The assessment carried out through several methods of interview, observation and assessment sheet. The capability level of the EDM04, APO07 and DSS01 process get capability level in level 3 with the targeted level in level 5 which is the same in each process, obtained the gap amount 2 and produced some recommendations that performed activities and made the documents related to each process.